(untitled) (Medico Legal Update, 2020)
Objective: This study aimed to assess the level of fear of childbirth and level of anxiety among primiparous women; and find out the relationship between fear of childbirth & level of anxiety and some socio demographical data of the sample. Methodology: A descriptive study, non-probability (Purposive) sample consist of 100 nulliparous pregnant women was carried out from November , 1st, 2018 to October, 10th, 2019 in (AL Salam) primary health care center and two hospitals (Azadi teaching & Kirkuk general) at gynecological consultation in Kirkuk city. To achieve the objectives of the study a developmental & constructed questionnaire conducted for the purpose of the study, which consisted of three parts: the socio-demographic characteristics; Anxiety scale for pregnancy (ASP) it consists of 14-items to determine the severity of the anxiety symptoms & the Wijma Delivery Expectancy/ Experience Questionnaires (W-DEQ) consist of 33 items was used to investigate fear of childbirth. Results: The majority of the pregnant women (39%) aged group (26-30years), (48%) was gestational age/ week 14-26 weeks, (33%) of them graduated from secondary school, regarding to the occupation (63%) was housewife, financial status was barely sufficient and constitute (86%), and (99%) of them from urban residency, tenant housing (82%), nucleus family type (86%), and (73%) of them preferred normal vaginal delivery mode and ( 96%) of the women were regularity antenatal visiting. Conclusions: The study detected a severity of the anxiety related pregnancy was moderate, and level of fear of childbirth was mild. Also founds a significant relationship between anxiety level and age of primiparous women.